Bernadottenes boksamling i Norge, 1814-1905 - Eide, Elisabeth S. (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
In 1905 the union between Sweden and Norway was dissolved. Oskar II of Sweden. decided to donate parts of his private belongings to the Norwegian state, including the book collections at the Palace and in a building called “Paléet”. The Royal University Library (UBO) was granted permission to take out whatever books they wanted. In 1905 the book collection amounted to about 5,500 volumes. The origins of the two book collections are traced, with special reference to the royal preferences of the kings Oskar I, Karl 15. and Oskar II. Possible Norwegian preferences in regards to the selection of books, and the role of the Norwegian keepers of the books are discussed. What function the royal collections had in Norway, and why the books were not kept together is also an issue in this article. The 4,000 volumes selected by UBO today form the “Slottsbiblioteket” at The national Library. At the Royal Palace the 1,500 volumes are kept together under the name of “Bernadottesamlingen” (The Bernadotte Collection). An investigation into what considerations played a part in the then librarian’s selection of books, and why the two collections have come to take the form they have today, takes place in the last part of the article.